[A cross-sectional study on the use of statin among patients with atherosclerotic ischemic stroke in China.] - Jiang, L; Li, X; Li, J; Feng, F; Chen, Y; Chen, Z; Martin, L; Jane, A (2010)
OBJECTIVE: To investigate the degree and determinants of the use on statin among patients with atherosclerotic ischemic stroke in China. METHODS: In the context of an international multi-center clinical trial being undertaken in China, 5585 patients with atherosclerotic ischemic stroke were screened in 39 prestigious hospitals in 10 cities. The characteristics collected through electronic questionnaire were described and analyzed. RESULTS: All the screened patients had indications for statins. Among those, 60% of the patients had a history from 3 months to 2 years of suffering from stroke. However, up to 80% of the patients were not using statins when screened. Even in those with statins, about 1/4 of the patients took statins for much shorter period than the history of stroke. The proportion using statins among IS patients with CHD was 4 times more than in those without CHD. Simvastatin and Atorvastatin were most commonly used. CONCLUSION: Statins were greatly underused for secondary prevention among patients with atherosclerotic ischemic stroke in China. There was a large gap between evidence and practice. It remains a major challenge for healthcare professionals and policy makers to tackle this problem more positively.